Development of Vitreoretinal Lymphoma in a Patient with Sarcoid Uveitis. (18th May 2020) - Wartique, Lucie; Jamilloux, Yvan; De Parisot De Bernecourt, Audrey; Kodjikian, Laurent; Ghesquieres, Hervé; Ide, Christophe; Sève, Pascal
ABSTRACT: Purpose: The purpose of this article is to report the first case of primary vitreoretinal lymphoma in a patient with sarcoid uveitis. Material and Methods: A 63-year-old woman with biopsy-proven sarcoid uveitis diagnosed 7 years ago was presented for a 6-month history of bilateral intermediate uveitis and gait disturbance with cerebral magnetic resonance imaging suggestive of neurosarcoidosis. Because of corticoids resistance, a vitrectomy and a cerebral biopsy were performed. The final diagnosis was primary central nervous system diffuse lymphoma. Patient died despite the chemotherapy with an initial improvement of visual and neurological features. Conclusion: Ophthalmologists should know that patient followed up with sarcoid uveitis can develop a primary vitreoretinal diffuse large B-cell lymphoma.